2018
DOI: 10.1002/acn3.545
|View full text |Cite
|
Sign up to set email alerts
|

Influenza‐like illness as a trigger for ischemic stroke

Abstract: ObjectiveWe hypothesized that ILI is associated with risk of incident stroke, and that the risk would be highest closest in time to the event.MethodsThis case‐crossover analysis utilized data obtained from the California State Inpatient Database of the Healthcare Cost and Utilization Project (HCUP). The outcome of interest was ischemic stroke. Exposure was defined as a visit to the emergency department or hospitalization for influenza‐like illness (ILI) 365, 180, 90, 30, or 15 days before stroke (risk period) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 32 publications
2
96
0
5
Order By: Relevance
“…Infection increases the odds of stroke by 1.4-fold particularly early in convalescence. 4 A similar relationship might be expected from infection by the novel coronavirus SARS-CoV-2, which causes COVID-19.…”
Section: Strokementioning
confidence: 74%
“…Infection increases the odds of stroke by 1.4-fold particularly early in convalescence. 4 A similar relationship might be expected from infection by the novel coronavirus SARS-CoV-2, which causes COVID-19.…”
Section: Strokementioning
confidence: 74%
“…The pathophysiology for the development of stroke in patients with COVID-19 is multifactorial. Infection, in general, may increase the odds of stroke 1.4-fold, particularly in the early convalescence phase, and this association may also be similarly expected among COVID-19 patients ( 17 ). Secondly, SARS-CoV-2 may potentially predispose to thrombogenesis and increase the risk of stroke by infecting the myocardium cells via ACE2 (angiotensin-converting enzyme II) receptor and causing vascular injury and inflammation ( 18 ).…”
Section: Introductionmentioning
confidence: 75%
“…The association of stroke with viral infection is well-established, albeit uncommon. In general, viral infection, particularly those in the early convalescence phase, increases the odds of stroke by 1.4-folds ( 17 ). A previous study amongst SARS-COV-1 patients showed that LVO occurred in a small percentage of patients (2.4%) that were infected in which the two patients had cardiac dysfunction, disseminated intravascular coagulation, and significant hypotension before the onset of stroke ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations illustrate large vessel occlusion associated with clotting induced by SARS-CoV-2 infection complicating underlying stable atherosclerotic disease. Complications of atherosclerotic disease by viral infection have previously been described [11,12] but the heavy burden of the current COVID outbreak has permitted an infrequent complication of atheroma associated with viral infection to be described. Direct (invasion by virus) or indirect mechanisms (inflammatory/procoagulant status) have also been debated [7,13].…”
Section: Discussionmentioning
confidence: 99%